ANALISIS RANTAI NILAI SAYURAN HIDROPONIK DI KECAMATAN KAO KABU-PATEN HALMAHERA UTARA (STUDI KASUS KELOMPOK TANI BINAAN PT. NUSA HALMAHERA MINERALS) (Analysis of Hydroponic Vegetables Chain Value in Kao District, North Halmahera Regency (Case Study of Farmer Group Fostered by PT. Nusa Halmahera Minerals) - Regina Clairine Papilaya; Theodora M. Katiandagho; Grace A. J. Rumagit (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
This study aims to analyze the value chain of hydroponic vegetables from the farmer groups fostered by PT. Nusa Halmahera Minerals. This study was conducted in September to November 2019. The data used in this study were primaryÂ and secondary data. Primary data were obtained through direct interviews with 17 respondents consisting of 12 farmers, 2 traders and 3 retailers, using a questionnaire. Secondary data were obtained from Hobata Farm, Central Statistics Agency (BPS), literature and previous research. The sampling method used was Purposive Sampling. The results showed that the margins generated by value chain actors were positive. This made every actor got benefit in the production and sale of hydroponic vegetables. Margin obtained from farmers was Rp. 850,504.-, collector traders was Rp. 245,000.-, and retailers was Rp. 432,500.-. All costs incurred by farmers in producing hydroponic vegetables were provided by PT. Nusa Halmahera Minerals.Keywords: Value chain, hydroponic vegetables, farmer groups